Orthopedic Injuries in Professional Surfers: A Retrospective Study at a Single Orthopedic Center. Issue 4 (July 2020) - Hohn, Eric; Robinson, Sean; Merriman, Jarrad; Parrish, Robin; Kramer, Warren
Abstract : Background: Literature regarding surfing injuries is scarce and most studies report a high number of minor injuries. Recent literature suggests that musculoskeletal injuries are more common than previously reported. In the mid 2000s, competitive surfing has seen an increase in aerial maneuvers, as they have become more highly rewarded by the judging panel, which may be contributing to a change in injury patterns. Our goal was to evaluate orthopedic injuries in professional surfers. Hypothesis: Orthopedic injuries in professional surfers are diverse and have evolved with skill and technology. Study Design: Retrospective observational study. Level of Evidence: Level 4 Case Series. Methods: Medical records of professional surfers from a single orthopedic center between 1991 and 2016 were reviewed. Injuries sustained while surfing and chronic injuries related to surfing were included. Site of injury, diagnosis, and treatment were recorded along with demographic data. Results: In total, 163 injuries in 86 athletes were recorded. The median injury age was 28.5 years (range 12-62 years) and 92.6% of patients were male. The most frequently injured body parts were the knee (28.2%), ankle (22.1%), and shoulder (19%). Most knee injuries were of the medial collateral ligament at 49%, with 75% of ankle injuries being sprains, and in shoulder, 48% had instability, 42% had a rotator cuff tear, and 35% had a superior anterior–posterior labral tear. Lower extremity injuries primarily affected the surfers' back leg (72.5%). In all, 34.6% of all injuries required surgical intervention and involved shoulder injuries most the time. Conclusions: The most common orthopedic injuries in professional surfers involve the knee, ankle, shoulder, hip, and back. Surfers' rear extremities were preferentially injured which is the extremity responsible for power and torque. Shoulder injuries increased the probability of an operative intervention. Last, overuse injuries (femoral-acetabular impingement, rotator cuffs) occurred in the older surf population compared with more acute injuries (ankle sprains/fractures, anterior cruciate ligament tears) which is also consistent with time to surgery.